2020
DOI: 10.3390/biomedicines8120620
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein-Targeted Therapies for Heart Failure

Abstract: The main and common constituents of high-density lipoproteins (HDLs) are apolipoprotein A-I, cholesterol, and phospholipids. Biochemical heterogeneity of HDL particles is based on the variable presence of one or more representatives of at least 180 proteins, 200 lipid species, and 20 micro RNAs. HDLs are circulating multimolecular platforms that perform divergent functions whereby the potential of HDL-targeted interventions for treatment of heart failure can be postulated based on its pleiotropic effects. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 151 publications
(203 reference statements)
0
14
0
Order By: Relevance
“…Importantly, apart from the aforementioned mimetic peptides, administration of apoA-I Milano nanoparticles has gained much attention for treating heart failure and coronary artery disease [ 303 , 304 , 305 ]. Briefly, apoA-I Milano is an apoA-I mutant resulting from an arginine 173 to cysteine mutation [ 306 , 307 ], leading to a higher life expectancy in heterozygotes and a lower atherosclerosis rate [ 304 ]. MDCO-216 is a form of reconstituted HDLs consisting of purified recombinant dimer apoA-I Milano complexed with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine [ 308 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, apart from the aforementioned mimetic peptides, administration of apoA-I Milano nanoparticles has gained much attention for treating heart failure and coronary artery disease [ 303 , 304 , 305 ]. Briefly, apoA-I Milano is an apoA-I mutant resulting from an arginine 173 to cysteine mutation [ 306 , 307 ], leading to a higher life expectancy in heterozygotes and a lower atherosclerosis rate [ 304 ]. MDCO-216 is a form of reconstituted HDLs consisting of purified recombinant dimer apoA-I Milano complexed with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine [ 308 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causal role of oxidative stress in heart failure is also supported by gene transfer studies of the three primary antioxidant enzymes (SODs, catalase, and glutathione peroxidase), of thioredoxin, and of heme oxygenase-1. Finally, multiple gene transfer prevention and intervention studies have demonstrated that gene therapy directed at the correction of metabolic risk factors resulted in a marked reduction of systemic oxidative stress and oxidative stress in the myocardium [63,64]. This correction of metabolic risk factors also resulted in improved cardiac function and prevention or reversal of pathological remodeling and heart failure [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, multiple gene transfer prevention and intervention studies have demonstrated that gene therapy directed at the correction of metabolic risk factors resulted in a marked reduction of systemic oxidative stress and oxidative stress in the myocardium [63,64]. This correction of metabolic risk factors also resulted in improved cardiac function and prevention or reversal of pathological remodeling and heart failure [63,64]. The broad robustness of the strong link between reduction of oxidative stress and prevention and treatment of heart failure suggests that reduction of oxidative stress is an important mediator of the observed effects of metabolic gene therapy on cardiac structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations